(Invited) The Dynamics of Nickelidation for Self-Aligned Contacts to InGaAs Channels. (16th August 2017) - Chen, Renjie; Dai, Xing; Jungjohann, Katherine L; Mook, William Moyer; Nogan, John; Soci, Cesare; Dayeh, Shadi
Abstract : The rapid development of ultrascaled III−V compound-semiconductor devices requires the detailed investigation of metal-semiconductor contacts at the nanoscale where crystal orientation, size, and structural phase play dominant roles in device performance. Here, we report comprehensive studies on the solid-state reaction between metal (Ni) and ternary III−V semiconductor (In0.53 Ga0.47 As) nanochannels to reveal their reaction kinetics, dynamics, formed crystal structure, and interfacial properties. We observed size-dependent reaction kinetics that are dominated by Ni surface-diffusion at small channel dimensions. We also employed in-situ heating in a transmission electron microscope (TEM) to record and analyze the atomic scale dynamics of contact reactions both in the cross-section and along the nanowire channel directions of InGaAs nanowires. Atomic models and nucleation models were introduced to depict the ledge formation and nucleation events. Deformation theory was applied to calculate the strain-induced shift in band-edge energies at the nickelide/InGaAs interface. These observations pave the way for engineered nanoscale contact to III-V transistors.